2009
DOI: 10.1021/jp8103485
|View full text |Cite
|
Sign up to set email alerts
|

Lower Critical Solution Temperature in the Metastable Region of an Ionic Solution in a Non-Polar Solvent

Abstract: Previous studies of the critical behavior of ionic solutions in nonpolar solvents showed mainly upper critical solution temperatures. Now, we report for the solution of tetra-n-butyl ammonium bromide (N4444Br) in toluene a nearly closed miscibility loop, where the lower critical solution temperature (Tc=297.75+/-0.05 K, xc=0.0270+/-5x10(-4)) is located in the region, which is metastable in respect to crystallization of the salt. The new observation is in variance to the former findings according to which the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 54 publications
2
13
0
Order By: Relevance
“…For (T * ,c)-diagrams in Fig. 3 (b), one can see the closed miscibility loops and the lower critical solution points (LCSP), the existence of which was also observed experimentally in [62] for ionic solutions in a non-polar solvent (the solution of N 4444 Br in toluene). However, it was shown in [62] that the phase transition related to the LCSP is located in a metastable region.…”
Section: Phase Diagrams Of the Rpm-hs Mixturesupporting
confidence: 64%
“…For (T * ,c)-diagrams in Fig. 3 (b), one can see the closed miscibility loops and the lower critical solution points (LCSP), the existence of which was also observed experimentally in [62] for ionic solutions in a non-polar solvent (the solution of N 4444 Br in toluene). However, it was shown in [62] that the phase transition related to the LCSP is located in a metastable region.…”
Section: Phase Diagrams Of the Rpm-hs Mixturesupporting
confidence: 64%
“…Systematic screening experiments for solutions of salts explore phase diagrams in the full range of solvents from non-polar hydrocarbons to water, the most polar solvent considered till now. Phase diagrams of solutions in linear [79], cyclic and [80] aromatic hydrocarbons [81][82][83][84], alcohols [85][86][87][88][89] and water [87] have been discovered and investigated in some detail. The ionic liquids, considered mostly, contain an imidazolium cation [80][81][82][85][86][87], but ionic liquids with phosphonium [79] or ammonium cations [83,84] [80,81,85,86].…”
Section: Experiments Determining the Nature Of The Critical Pointmentioning
confidence: 99%
“…Phase diagrams of solutions in linear [79], cyclic and [80] aromatic hydrocarbons [81][82][83][84], alcohols [85][86][87][88][89] and water [87] have been discovered and investigated in some detail. The ionic liquids, considered mostly, contain an imidazolium cation [80][81][82][85][86][87], but ionic liquids with phosphonium [79] or ammonium cations [83,84] [80,81,85,86]. Figure 3 shows www.cpp-journal.org as example of a typical ionic liquid the structure of Butyl-methyl-imidazolium bis(trifluormethyl sulfonyl)imide (C 4 mim(CF 3 SO 2 ) 2 N) Most phase diagrams show an upper critical solution point as expected from simulations of the RPM, but phase diagrams with a lower critical solution point [23,90], closed solubility loop [84] and more complicated phase diagrams [81] have been observed as well.…”
Section: Experiments Determining the Nature Of The Critical Pointmentioning
confidence: 99%
See 1 more Smart Citation
“…There are a few reports of the LCST-type phase transition of mixtures containing alkylammonium salts and molecular liquids. [18][19][20][21][22] Seddon et al reported that IL/chloroalkane [23] and IL/aromatic hydrocarbon [24] mixtures exhibited both UCST and LCST behaviour. We recently reported that ILs containing amino acid anions with a trifluoromethanesulfonyl group on the amino group and alkylphosphonium cations underwent a clear phase separation with water at room temperature; the homogeneous phase was obtained upon cooling.…”
Section: Introductionmentioning
confidence: 99%